Potentially Important Therapeutic Interactions between Antibiotics, and a Specially Engineered Emulsion Drug Vehicle Containing Krill-Oil-Based Phospholipids and Omega-3 Fatty Acids - David F. Driscoll (MDPI AG, 2018)
The incidence of antimicrobial resistance (AMR) worldwide is increasing as the pipeline for the development of new chemotherapeutic entities is decreasing. Clearly, overexposure to antibiotics, including excessive dosing, is a key factor that fuels AMR. In fact, most of the new antibacterial agents under development are derivatives of existing classes of antibiotics. Novel approaches involving unique antimicrobial combinations, targets, and/or delivery systems are under intense investigation. An innovative combination of active pharmaceutical ingredients (APIs) consisting of antimicrobial drug(s), krill-oil-based phospholipids, and omega-3 fatty acid triglycerides, that may extend the therapeutic viability of currently effective antibiotics, at least until new chemical entities are introduced, is described.